cAMP Signaling of Adenylate Cyclase Toxin Blocks the Oxidative Burst of Neutrophils through Epac-Mediated Inhibition of Phospholipase C Activity - Cerny, Ondrej; Anderson, Karen E; Stephens, Len R; Hawkins, Phillip T; Sebo, Peter (Journal of immunology (Baltimore, Md., 2017)
The adenylate cyclase toxin-hemolysin (CyaA) plays a key role in immune evasion and virulence of the whooping cough agent Bordetella pertussis. CyaA penetrates the complement receptor 3-expressing phagocytes and ablates their bactericidal capacities by catalyzing unregulated conversion of cytosolic ATP to the key second messenger molecule cAMP. We show that signaling of CyaA-generated cAMP blocks the oxidative burst capacity of neutrophils by two converging mechanisms. One involves cAMP/protein kinase A-mediated activation of the Src homology region 2 domain-containing phosphatase-1 (SHP-1) and limits the activation of MAPK ERK and p38 that are required for assembly of the NADPH oxidase complex. In parallel, activation of the exchange protein directly activated by cAMP (Epac) provokes inhibition of the phospholipase C by an as yet unknown mechanism. Indeed, selective activation of Epac by the cell-permeable analog 8-(4-chlorophenylthio)-2'-O-methyladenosine-3',5'-cyclic monophosphate counteracted the direct activation of phospholipase C by 2,4,6-trimethyl-N-[3-(trifluoromethyl)phenyl]benzenesulfonamide. Hence, by inhibiting production of the protein kinase C-activating lipid, diacylglycerol, cAMP/Epac signaling blocks the bottleneck step of the converging pathways of oxidative burst triggering. Manipulation of neutrophil membrane composition by CyaA-produced signaling of cAMP thus enables B. pertussis to evade the key innate host defense mechanism of reactive oxygen species-mediated killing of bacteria by neutrophils.
Keywords: signální transdukce; Protein Kinase C; Respiratory Burst; AMP cyklický; reaktivní formy kyslíku; respirační vzplanutí; Signal Transduction; Type C Phospholipases; Neutrophils; Phosphatidylinositol 3-Kinases; Cyclic AMP; fosfatidylinositol-3-kinasy; Reactive Oxygen Species; Bordetella pertussis; Extracellular Signal-Regulated MAP Kinases; fosfolipasy typu C; Humans; proteinkinasa C; Guanine Nucleotide Exchange Factors; neutrofily; mitogenem aktivované proteinkinasy p38; extracelulárním signálem regulované MAP kinasy; adenylátcyklasový toxin; Adenylate Cyclase Toxin; p38 Mitogen-Activated Protein Kinases; výměnné faktory guaninnukleotidů; lidé